First-Year Undergraduate Students’ Experiences of Social Integration at Universities in Azerbaijan - Mehdiyeva, Fatima (My University, 2026)
This research investigates the social experiences of first-year undergraduate students in Azerbaijan during their transition from school to university. Although social integration is considered an important factor influencing students’ well-being and academic success, limited qualitative research has examined how students in Azerbaijan experience this process. The study addressed two research questions: (1) How do undergraduate students in Azerbaijan describe their experiences of social integration and personal development during their transition to university life? and (2) What factors facilitate or hinder their social integration? The study adopted a qualitative interpretivist approach. Data were collected through semi-structured interviews with 10 first- and second-year undergraduate students from two universities in Baku. The data were analyzed using thematic analysis to identify key patterns in students’ experiences. The findings showed that the process of social integration took place gradually and involved a range of emotions. During the initial period following the transition into university, students experienced a range of negative emotions. However, as the students began to interact with their peers and become more familiar with the university environment, they began to feel a sense of belonging to the institution. The main factor that was found to facilitate the social integration of students into the university community was the development of relationships with their peers. The other factors that were found to pose challenges to the social integration of students included their academic workload, language barriers, and lack of support systems within the university. Furthermore, the social integration of students was found to contribute to their personal growth within areas such as confidence and independence. Overall, this study contributes to the limited available qualitative literature regarding higher education in Azerbaijan and highlights the importance of support systems within universities.
Keywords: Social Integration; University Transition; First-Year Students; Undergraduate Students; Higher Education; Student Experiences; Sense of Belonging; Peer Relationships; Personal Development